Building resilient IP networks - Lee, Kok-Keong.; Lim, Fung.; Ong, Beng-Hui. (Indianapolis, Ind. : Cisco Press, 2006)
Teaches how an IP network can be broken down to various modules and how these modules interconnect with one another and explores new network resiliency features that have been developed recently, categorized with respect to the design modules.
Includes index.
"The practical guide to building resilient and highly available IP networks"--Cover.
oif 24/06/15
Loan
Keywords: TCP/IP (Computer network protocol); Computer networks